Exercise performance in Ebstein's anomaly in the course of time — Deterioration in native patients and preserved function after tricuspid valve surgery. (1st September 2016) - Müller, Jan; Kühn, Andreas; Tropschuh, Andrea; Hager, Alfred; Ewert, Peter; Schreiber, Christian; Vogt, Manfred
Abstract: Objective: The purpose of this study was to assess the longitudinal follow-up of exercise performance in patients with native Ebstein anomaly and patients who had received previous tricuspid valve surgery. Patients and methods: We identified 59 patients with Ebstein anomaly who had performed at least two cardiopulmonary exercise tests within a minimum of 6 months. 22 patients (15 female, 29.0 ± 13.4 years) with native conditions, 37 patients (21 female, 32.1 ± 15.3 years) had undergone surgery of their tricuspid valve before baseline testing. Results: In the non-operated group peak workload (2.58 ± 0.7 to 2.38 ± 0.7 W/kg, p = .019) declined during a mean follow-up of 4.6 ± 2.6 years, whereas peak workload remained stable in the surgical group (2.02 ± 0.6 to 2.06 ± 0.7 W/kg, p = .229) throughout the follow-up of 3.4 ± 2.3 years. In the 18 patients who had their surgery less than one year prior to the first CPET the exercise performance even increased during the follow-up. Peak blood pressure as a marker of cardiac adaption to exercise increased in the follow-up examination only in the surgical group (159 ± 23 vs. 171 ± 30 mm Hg, p = .007). In the non-operated group blood pressure remained unchanged at follow-up (161 ± 26 vs. 166 ± 29, p = .358). Conclusion: Exercise performance deteriorates in non-operated patients with Ebstein anomaly in contrast to patients after tricuspid valve surgery where exercise performance remains stable. These facts promote a surgical intervention latest at the time when exercise performance decreases.